Melatonin-Induced Transcriptome Variation of Sweet Potato Under Heat Stress - Mengzhao Wang; Yang Zhou; Bei Liang; Sunjeet Kumar; Wenjie Zhao; Tianjia Liu; Yongping Li; Guopeng Zhu (Plants)
Melatonin (MT) has been widely recognized for its ability to mitigate the effects of abiotic stress and regulate plant development. In this study, we investigated the role of exogenous MT in enhancing heat tolerance in sweet potato, with a particular focus on its capacity to alleviate heat stress-induced damage. MT treatment significantly reduced oxidative stress, as evidenced by decreased levels of hydrogen peroxide, superoxide ions, and malondialdehyde (MDA), all of which were elevated under heat stress. To uncover the underlying mechanisms, RNA sequencing was performed on three experimental groups: control (CK), heat stress alone (HS), and MT pre-treatment followed by heat stress (MH). A total of 3491, 3280, and 1171 differentially expressed genes (DEGs) were identified in the CK vs. HS, CK vs. MH, and HS vs. MH comparisons, respectively. MT treatment notably modulated the expression of genes involved in redox regulation and nicotinate and nicotinamide metabolism. Moreover, MT enhanced the expression of genes associated with key signaling pathways, including mitogen-activated protein kinases (MPK3) and plant hormone signal transduction components, such as ethylene response factor (ERF). These findings offer novel insights into the mechanisms by which exogenous MT enhances heat tolerance in sweet potato, highlighting its role in regulating antioxidant systems, metabolic pathways, and hormone signaling. This study presents valuable strategies for improving crop resilience to heat stress.